Computed Tomography Angiography for the Chimeric Anterolateral Thigh Flap in the Reconstruction of the Upper Extremity - Zhang, Yan; Pan, Xiaoyun; Yang, Hong; Yang, Ying; Huang, Hai; Rui, Yongjun (Journal of Reconstructive Microsurgery, 2017)
Background The chimeric anterolateral thigh (ALT) flap has been an ideal option for restoring complex soft tissue defects. However, as the vascular anatomy of the ALT is variable, the positions of its perforators are uncertain, which makes the surgery more challenging. Therefore, our study utilized computed tomographic angiography (CTA) for preoperative perforator mapping.Methods From October 2013 to October 2015, 37 patients suffering upper extremity soft tissue defects underwent CTA before ALT flap reconstruction. Perforators originating from the same source vessel were mapped by CTA, and the donor thigh and preferred perforators were selected accordingly. All preoperative parameters of perforators detected by CTA were checked during operation.Results Thirty-three dual-skin paddles, three tri-skin paddles, and one quad-skin paddles flap were designed and used in this study. Eighty-seven perforators were mapped by CTA preoperatively. Seventy-nine (90.8%) were used; 97.5% of these were musculocutaneous and 2.5% septocutaneous. All perforators used intraoperatively were consistent with preoperative parameters. Post-operatively, 2 patients experienced complications but there was 100% flap survival overall. The donor sites primarily underwent primary closure, apart for 7 cases which underwent skin grafting. There was no donor site morbidity.Conclusion Preoperative mapping by CTA is a useful, fast, and noninvasive method for assessing the source vessels, and can be a significant aid in chimeric ALT flap surgery.
Keywords: chimeric anterolateral thigh flap; soft tissue reconstruction; computed tomography angiography